2011
DOI: 10.1177/1352458511399798
|View full text |Cite
|
Sign up to set email alerts
|

Olfactory threshold is impaired in early, active multiple sclerosis

Abstract: We report evidence for qualitatively distinct hyposmia in MS, with increased smell threshold in the early inflammatory phases of the disease and impaired identification with a more widespread chronic disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
85
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(97 citation statements)
references
References 23 publications
(40 reference statements)
9
85
3
Order By: Relevance
“…The correlation between identification ability and the EDSS score is consistent with data from the literature [8]. Another study demonstrated that the longer the disease had progressed, the greater the damage to odor identification [9]. Our study did not statistically validate this correlation.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…The correlation between identification ability and the EDSS score is consistent with data from the literature [8]. Another study demonstrated that the longer the disease had progressed, the greater the damage to odor identification [9]. Our study did not statistically validate this correlation.…”
Section: Discussionsupporting
confidence: 80%
“…Olfactory dysfunction also seems to be correlated to disability in patients, as shown by the Expanded Disability Status Scale (EDSS) score [8]. Data on the correlation between olfaction and quality of life or depression are inconsistent in the literature [6,9,10]. A recent study showed that olfactory function is significantly damaged in MS patients, affecting both the ability to identify odors and the detection threshold.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Olfactory testing has been used as a preclinical indicator to predict the development and onset of diseases such as Parkinson's disease [10], multi-infarct dementia [11], multiple sclerosis [12] and Alzheimer's disease [11]. Previous studies have further reported a relationship between olfactory dysfunction and diabetes [13][14][15][16][17][18], as well as an inverse relationship between olfactory identification and discrimination scores and the presence of diabetic complications [13,14,16,19,20].…”
Section: Introductionmentioning
confidence: 99%
“…Limited cross-sectional studies have explored associations between diabetes and olfaction [13][14][15][16][17][18][19][20]37] with inconsistent findings (Table 2 [ [11][12][13][14][15][16][17][18]35,[38][39][40]). The variability in outcomes may be attributed to several methodological inconsistencies, such as selection bias, small sample sizes, comorbidities, lack of objective measures, and differences in diagnostic tests for olfactory dysfunction, and diabetes and its complications.…”
Section: Diabetes Mellitus and Olfactory Dysfunctionmentioning
confidence: 99%